Biomechanics and functional morphology of a climbing monocot. (18th August 2015) - Hesse, Linnea; Wagner, Sarah T.; Neinhuis, Christoph
Abstract : Climbing monocots can develop into large bodied plants despite being confined by primary growth. In our study on Flagellaria indica we measured surprisingly high stem biomechanical properties (in bending and torsion) and we show that the lack of secondary growth is overcome by a combination of tissue maturation processes and attachment mode. This leads to higher densities of mechanically relevant tissues in the periphery of the stem and to the transition from self-supporting to climbing growth. The development of specialised attachment structures has probably underpinned the evolution of numerous other large bodied climbing monocot taxa. Abstract: Plants with a climbing growth habit possess unique biomechanical properties arising from adaptations to changing loading conditions connected with close attachment to mechanical supports. In monocot climbers, mechanical adaptation is restricted by the absence of a bifacial vascular cambium. Flagellaria indica was used to investigate the mechanical properties and adaptations of a monocot climber that, uniquely, attaches to the surrounding vegetation via leaf tendrils. Biomechanical methods such as three-point bending and torsion tests were used together with anatomical studies on tissue development, modification and distribution. In general, the torsional modulus was lower than the bending modulus; hence, torsional stiffness was less than flexural stiffness. Basal parts of mature stems showed the greatest stiffness while that of more apical stem segments levelled off. Mechanical properties were modulated via tissue maturation processes mainly affecting the peripheral region of the stem. Peripheral vascular bundles showed a reduction in the amount of conducting tissue while the proportion and density of the bundle sheath increased. Furthermore, adjacent bundle sheaths merged resulting in a dense ring of fibrous tissue. Although F. indica lacks secondary cambial growth, the climbing habit is facilitated by a complex interaction of tissue maturation and attachment.